2016
DOI: 10.1136/neurintsurg-2016-012462
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved 3D rotational angiography: display of detailed neurovascular anatomy in patients with intracranial vascular malformations

Abstract: Time-resolved 3DRA with 4D VRTs and MPRs is technically feasible and provides a detailed display of the angioarchitecture at the fistulous point or the nidus. Visualization of all angiographic features demands additional post-processing. Further standardization of evaluation tools and studies with blinded independent reviewers are necessary before the new technique can replace conventional neuroangiographic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 6 publications
0
40
1
Order By: Relevance
“…In line with recent literature, qualitative parameters obtained from 4D DSA also demonstrated excellent agreement with 2D DSA in our series regarding image quality and arteriovenous visualization of the angioarchitecture of the pathology. Sandoval-Garcia et al 8 and Lescher et al 9 observed a superior visualization of intranidal structures and the fistulous point of a dAVF, respectively, with 4D DSA because time-resolved 3D imaging enables easy differentiation of arterial and venous structures. We fully agree with the hypothesis of Sandoval-Garcia et al that 4D DSA might simplify the understanding of complex vascular malformations and provides valuable support in risk assessment and therapeutic strategies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In line with recent literature, qualitative parameters obtained from 4D DSA also demonstrated excellent agreement with 2D DSA in our series regarding image quality and arteriovenous visualization of the angioarchitecture of the pathology. Sandoval-Garcia et al 8 and Lescher et al 9 observed a superior visualization of intranidal structures and the fistulous point of a dAVF, respectively, with 4D DSA because time-resolved 3D imaging enables easy differentiation of arterial and venous structures. We fully agree with the hypothesis of Sandoval-Garcia et al that 4D DSA might simplify the understanding of complex vascular malformations and provides valuable support in risk assessment and therapeutic strategies.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, Sandoval-Garcia et al 7,8 have shown the clinical feasibility of 4D DSA both in a canine model and in patients, with promising results. Recently, the detailed analysis of dAVFs and AVMs with 4D DSA of Lescher et al 9 demonstrated a significantly improved visualization of a fistulous point of the dAVF or a nidus of the AVM by using 4D DSA; in many cases, 4D DSA even came close to superselective angiography.…”
mentioning
confidence: 99%
“…While experience with this application is still limited, early evaluations have shown some advantages over conventional 3D DSA in evaluation of complex AVMs and AVFs. 9,10,11,12 In our experience and in previous reports, the 4D studies have been particularly helpful in assessment of the angioarchitecture of the nidus of AVMs and the location of the fistula connections in AVFs. 10 11.…”
Section: Discussionmentioning
confidence: 65%
“…The review of Rammos et al 1 is lacking a discussion on advanced imaging tools that may help to demonstrate these aneurysms and further our understanding of their origin. Indeed, high-rate (6 frames per second or more) DSA acquisitions, 3D rotational angiography (RA), 4D-RA technology, 11 and ultraselective angiography, or even more recent algorithms used on 3D-RA such as segmentation algorithms 12 or anamorphosis algorithm, 13 may help to depict these aneurysms more accurately. Wall enhancement of the intranidal aneurysm on MR imaging has also been proposed as a radiologic feature that may help to confirm the bleeding site.…”
mentioning
confidence: 99%